The Biosafety Regulatory Approach and Governance Mechanism of GM Crops in the Philippines - Leonardo N. Pasquito (Indonesian Association for Public Administration (IAPA), 2019)
This paper analyzes the government biosafety regulatory approach to genetically modified (GM) crops in the Philippines focusing on the interplay and politics of the different government agencies (DOST-DOH-DENR-DA-DILG) that comprises the National Biosafety Committee of the Philippines (NBCP) in terms of entry permit applications of multinational companies, field trials, environmental assessment, health impact assessment, local supervision and regulation, commercial release and market test, nutritional study, and GMO product labelling. The study examines the regulatory policies of the Philippine government including local ordinances which aimed to support or discourage agricultural biotechnology innovations in the Philippines. Further, the paper investigates how the NCBP regulates the stakeholders’ debate on the risks and benefits of GMOs to the environment, human and animal health, and its impact on the food security program of the country. The study argues that the Philippine government is gradually losing its grip on the implementation of biosafety regulations and that invoking the precautionary principle, there is a need to resolve disputes in favor of the constitutional right to a balanced and healthful ecology of the people. The lack of dialogue and participatory public consultation to prevent clashing of interests on the conduct of field trials resulted in endless GMO war and debate. Thus, the study further noted that at present there is a looming deadlock on the debate of GMO between stakeholders which eventually is creating snail-pace agricultural biotechnology innovations and consequently stalling the food security program of the country.